Enhancing food safety and cultivated meat production: exploring the impact of microplastics on fish muscle cell proliferation and differentiation - Sun, Taozhu; Timoneda, Alfonso; Banavar, Amiti; Ovissipour, Reza (Frontiers in Food Science and Technology, 2024)
Cultivated meat, a sustainable alternative to traditional livestock farming, has gained attention for its potential environmental and health benefits. However, concerns about microplastic contamination pose challenges, especially when sourcing cells from marine organisms prone to microplastic bioaccumulation. Additionally, the pervasive presence of microplastics in laboratory settings, ingredients, and during the production, increases the risk of unintentional contamination. This study focused on Atlantic mackerel (Scomber scombrus) skeletal muscle cell lines to examine the effects of microplastic exposure, represented by fluorescent polyethylene microspheres (10–45 µm) on cell performance including cell proliferation, cell viability, gene expression, and differentiation processes critical for cultivated meat production. The results revealed significant impacts on cell attachment and proliferation at microplastic concentrations of 1 μg/mL, 10 μg/mL, and 50 μg/mL. Notably, the 10 μg/mL concentration exerted the most pronounced effects on cell viability during both attachment and proliferation phases. While the results indicated that both microplastic concentration and size influence cell viability, cell differentiation remained unaffected, and additional contributing factors require further investigation. These findings underscore the necessity of thoroughly exploring microplastic-cell interactions to ensure food safety and safeguard health within the burgeoning cultivated meat industry.